2018
DOI: 10.1103/physrevlett.121.067601
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Energetics and Correlation-Driven Metal-Insulator Transitions: The Case of Ca2RuO4

Abstract: This Letter uses density functional, dynamical mean field, and Landau-theory methods to elucidate the interplay of electronic and structural energetics in the Mott metal-insulator transition. A Landau-theory free energy is presented that incorporates the electronic energetics, the coupling of the electronic state to local distortions and the coupling of local distortions to long-wavelength strains. The theory is applied to Ca_{2}RuO_{4}. The change in lattice energy across the metal-insulator transition is com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…Earlier dynamical mean field theory (DMFT) calculations of the MIT in Ca 2 RuO 4 predict that the full d xy orbital polarization with n xy  ≈ 2, n xz  ≈  n yz  ≈ 1 and p  =  n xy  − ( n xz  +  n yz )/2 ≈ 1 observed in the insulating state vanishes in the metallic L-Pbca phase 4,7,14,16,38,39 . This is qualitatively consistent with our experiments showing signatures of all three t 2 g orbitals on the Fermi surface.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Earlier dynamical mean field theory (DMFT) calculations of the MIT in Ca 2 RuO 4 predict that the full d xy orbital polarization with n xy  ≈ 2, n xz  ≈  n yz  ≈ 1 and p  =  n xy  − ( n xz  +  n yz )/2 ≈ 1 observed in the insulating state vanishes in the metallic L-Pbca phase 4,7,14,16,38,39 . This is qualitatively consistent with our experiments showing signatures of all three t 2 g orbitals on the Fermi surface.…”
Section: Resultsmentioning
confidence: 98%
“…Mott 2 , realistic numerical studies point to a far more important role of structural changes in stabilizing the Mott state of archetypal insulators 3,4 . This, together with recent theoretical advances, has led to renewed interest in the interplay of lattice energetics and electronic properties near Mott transitions 57 . Hydrostatic and uniaxial pressure is particularly important in the experimental study of Mott transitions and also has a profound effect on other emerging properties of quantum materials 1,812 .…”
Section: Introductionmentioning
confidence: 99%
“…Some first-principles studies on strongly correlated oxides have highlighted the important effect structural disorder/defects may have on the energy barriers between different magnetic states. 20,21 Similarly, a recent study demonstrated that structural distortions associated with replacing V with Cr are responsible for enhanced correlation effects and stabilizing an insulating state at high temperatures. 22 It was also shown that despite Cr and V having different number of electrons such a replacement does not result in charge doping.…”
Section: A General Considerationsmentioning
confidence: 98%
“…All −43.9 202.2 −0.25 0.4 All −44.6 205.1 −0.25 2.2 > 170 −43.0 199.7 −0.25 4.4 > 190 −43.5 200.7 −0.25 TABLE I. Variable Range Hopping regime fitting parameters b. Crystallographic axes vs RuO distances By means of DFT+U calculations, A. Millis and coworkers32 found a transformation matrix relating the variations of the crystallographic axis δa, δb and δc to the variations of the Ru − O distances in the RuO 6 octahedra, that is, δx, δy and δz:…”
mentioning
confidence: 99%